RESPONITAS NEGARA TERHADAP STANDAR PRE-FLIGHT DALAM PENERBANGAN DOMESTIK DI BANDAR UDARA INTERNASIONAL NGURAH RAI (STUDI KASUS: PENANNGANAN MANAJEMEN BENCANA ANGKASA PURA I GUNUNG RINJANI TAHUN 2015 - Tamara, Kadek Tania (Jurnal Nawala Politika; 2017, 2017)
ABSTRACT   This research reviews disaster management and pre-flight standard in domestic flight service at Bali Ngurah Rai International Airport. This research used descriptive qualitative method with in-depth interview and field study, beside that this research also used library study related to the problem studied. In this study which Angkasa Pura I as airport manager in disaster management related to response, recovery, and development where the activities conducted before and after the disaster occurred. Response is an action taken before and after the impact of a disaster to save lives, possessions, and who deal with direct disruption, damage to other effects caused by a disaster. Recovery is the process by which people and government helped to return to previous life functions after a disaster. And development is the relationship between disaster-related activities and national development intended to ensure that disaster outcomes are effectively reflected in future policies for the benefit of national progress. And how Angkasa Pura I in conducting response, recovery, and development towards standard of pre-flight in domestic flight service that formed in land operation management system. In the aerospace world, there are three main stages of service: pre-flight service, in flight service, and post flight service. Pre-flight service is the handling of passengers and aircrafts prior to departure (at the airport of origin).   Keywords: Disaster management, Pre-flight service, response.